The Ellipsoid Zone Is a Structural Biomarker for Visual Outcomes in Diabetic Macular Edema and Macular Hole Management - Shivani Chaturvedi; Amisha Paul; Samya Singh; Levent Akduman; Sandeep Saxena (Vision)
Objectives: The goal was to study the ellipsoid zone (EZ) as a structural biomarker for final visual outcomes after pharmacological intervention in center-involving diabetic macular edema (DME) and surgical intervention for full-thickness macular holes (FTMHs). Methods: This was a tertiary care center-based retrospective study. After sample size calculations, data from 64 consecutive cases were collected, with subjects aged between 40 and 60 years. Thirty-two cases of DME with anti-vascular endothelial growth factor (VEGF) therapy and 32 cases of FTMHs with successful macular hole surgery (MHS) were studied. Spectral-domain optical coherence tomography (SD-OCT) data were collected. Measurements of EZ defects documented at the time of presentation and 12 weeks after intervention were analyzed using the caliper function of the machine. EZ restoration was graded, and a Pearson correlation analysis was performed. Results: Mean logMAR VA decreased after intravitreal therapy (IVT) from 1.12 ± 0.22 pre-intervention to 0.81 ± 0.41 post-intervention and after MHS, from 1.05 + 0.25 to 0.62 + 0.11 (p < 0.001). EZ disruption reduced from 73.4% to 19.4% after IVT and from 67% to 19.3% after MHS. DME and MHS postoperative visual acuity and residual EZ defect were observed to have a statistically significant linear correlation (r = 0.794, p < 0.001 and r = 0.894, p < 0.001, respectively). The EZ was found to be an excellent structural biomarker for final BCVA (area under curve = 0.95 for DME and 1.00 for MHS). Conclusion: Notable EZ restoration results were obtained from pharmacological and surgical interventions. The EZ proves to be a critical structural biomarker for predicting visual outcomes in center-involving DME and MHS.